Characterization of TbPH1, a kinetoplastid-specific pleckstrin homology domain containing kinesin-like protein - Kaltenbrunner, Sabine (Jihočeská univerzita, 2017)
The aim of this master thesis was the investigation of the uncharacterized protein TbPH1, by in silico studies, determining effects of its knock-down, studying the effect of a knock-down on the cell cycle, examining its cellular localization, and finding out about possible complexes and interaction-partners.
Characterization of TbPH1, a kinetoplastid-specific pleckstrin homology domain containing kinesin-like protein
Keywords: Trypanosoma brucei; RNAi; cell cycle; localization; TbPH1; TbKIF11; Trypanosoma brucei; RNAi; cell cycle; localization; TbPH1; TbKIF11